PRELIMINARY ECONOMIC ANALYSIS OF SPINY LOBSTER, Panulirus homurus CULTURE IN FLOATING NET CAGE IN EKAS BAY EAST LOMBOK - Anak Agung Alit; Titiek Aslianti; Bejo Slamet (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
Spiny lobster, Panulirus homurus